Tumbuhan Keanekaragaman Tumbuhan Bunga Liar di Cagar Alam Bantarbolang Pemalang Jawa Tengah - Ferdinand Fitria; Pudji Widodo; Ani Widyastuti (Fakultas Biologi Universitas Jenderal Soedirman, 2019)
Wild flowering plants that are included in the understorey are plant communities that make up lower stratification near the surface of the ground. Effects of forest boundaries can be seen from gradual changes in microclimates and vegetation patterns from the edge of the forest to the forest. The impact of meeting these two different environmental conditions for plants and animals is called edge effect. Forest boundaries also have an impact on changes in environmental factors including temperature, humidity, light intensity, soil pH and canopy cover. These factors are thought to influence the diversity of wild flowering plants. The results of the study showed that there were 43 species of wild flowering plants in Bantarbolang Nature Reserve with a total of 978 individuals included in 22 families. The most common type is Piper caducibrachteum as many as 183 individuals. The edge effect has an effect on the diversity of wild flowering plants as evidenced by the increasing number of species obtained tends to be less. Wild flowering plants that have the highest index of importance are Piper betle (66.55%) followed Piper caducibrachteum (52.44%) and Ageratum conyzoides (46.17%). The most influential environmental factors in wild flowering plant diversity are light intensity. The intensity of the light getting deeper into the forest is lower because the sunlight entering the forest is blocked by tree canopies.